Faktor yang mepengaruhi Keputusan Pembelian Ulang pada Forum Jual Beli - Prabowo, Yulius Denny; Rusli, Muhammad (LPPM of STIMIK ESQ, 2017)
The ease of access to the internet is and the rapid development of gadgets technology that encourage people to interact with the virtual world, the use of social media and the internet which was originally used as a means to interact with others shifted into the media to market the product. Kaskus as the largest online portal in Indonesia are keen to see the trend and create a trading forum on its website that can be used by anyone to offer their products or services. For sellers in this forum to get customers is not easy, it is necessary to understand the factors that influence a buyer to re-purchase the seller in this forum. Based on sampling buyers in this forum, it finds that the trust factor to the reputation of the seller and the services provided by the seller is the dominant factor affecting decisions to the buyers repeat order.